IMPLEMENTASI LEARNING MANAGEMENT SYSTEM (LMS) DENGAN METODE SCRUM DI SMK CYBER MEDIA UTAMA - Roeslan Djutalov; Sajida Nur Hasannah; Ahmad Fikriyadi; Nurman Dwi Sulistyo (Journal of Research and Publication Innovation, 2023)
The purpose of carrying out this practical work is to fulfill the requirements for thesis preparation, to develop the implementation of a Learning Management System (LMS) for administrators, teachers and students at Cyber Media Utama Vocational School. This practical work activity method begins with the preparation stage and field survey. Followed by a discussion with the parties, namely the principal of the Vocational Middle School Cyber Media Utama Vocational School which is located in the Kalisuren Village area, Kec. Tajurhalang District. Bogor- West Java. To identify the needs and opportunities required by Administrators, Teachers and Students of Cyber Media Utama Vocational School, then the socialization and training stage is carried out by the team. The results of this research are that administrators, teachers and students at Cyber Media Utama Vocational School can use and develop the Learning Management System (LMS) that has been created and can create or add learning methods according to school needs.